Thinking Style as a Predictor of Men's Participation in Cancer Screening. (March 2017) - McGuiness, Clare E.; Turnbull, Deborah; Wilson, Carlene; Duncan, Amy; Flight, Ingrid H.; Zajac, Ian
Men's participation in cancer screening may be influenced by their thinking style. Men's need for cognition (NFC) and faith in intuition were measured to explore whether they varied by demographic variables or predicted screening behavior. Australian males ( n = 585, aged 50-74 years) completed surveys about past screening and were subsequently offered mailed fecal occult blood tests (FOBTs). Demographic predictors included age, socioeconomic status, educational attainment, and language spoken at home. The screening behaviors were self-reported prostate cancer screening (prostate-specific antigen testing and digital rectal examinations [DREs]), and colorectal cancer screening (self-reported FOBT participation and recorded uptake of the FOBT offer). Analysis comprised principal component analysis and structural equation modelling. NFC was positively related to demographic variables education, socioeconomic status, and speaking English at home. Faith in intuition was negatively related to educational attainment. NFC predicted variance in self-reported DRE participation ( r = .11, p = .016). No other relationships with thinking style were statistically significant. The relationship of NFC to DRE participation may reflect the way certain attributes of this screening method are processed, or alternatively, it may reflect willingness to report participation. The relationship of thinking style to a range of healthy behaviors should be further explored.